Controllable Heterogenous Seeding‐Induced Crystallization for High‐Efficiency FAPbI3‐Based Perovskite Solar Cells Over 24%. Issue 36 (10th August 2022) - Zhang, Hengkai; Ren, Zhiwei; Liu, Kuan; Qin, Minchao; Wu, Zehan; Shen, Dong; Zhang, Yaokang; Chandran, Hrisheekesh Thachoth; Hao, Jianhua; Lee, Chun‐sing; Lu, Xinhui; Zheng, Zijian; et al.
Abstract: The addition of small seeding particles into a supersaturated solution is one among the most effective approaches to obtain high‐quality semiconductor materials via increased crystallization rates. However, limited study is conducted on this approach for the fabrication of perovskite solar cells. Here, a new strategy—"heterogenous seeding‐induced crystallization (hetero‐SiC)" to assist the growth of FAPbI3 ‐based perovskite is proposed. In this work, di‐ tert ‐butyl(methyl)phosphonium tetrafluoroborate is directly introduced into the precursor, which forms a low‐solubility complex with PbI2 . The low‐solubility complex can serve as the seed to induce crystallization of the perovskite during the solvent‐evaporation process. Various in situ measurement tools are used to visualize the hetero‐SiC process, which is shown to be an effective way of manipulating the nucleation and crystal growth of perovskites. The hetero‐SiC process greatly improves the film quality, reduces film defects, and suppresses nonradiative recombination. A hetero‐SIC proof‐of‐concept device exhibits outstanding performance with 24.0% power conversion efficiency (PCE), well over the control device with 22.2% PCE. Additionally, hetero‐SiC perovskite solar cell (PSC) stability under light illumination is enhanced and the PSC retains 84% of its initial performance after 1400 h of light illumination. Abstract : Heterogenous seeding‐induced crystallization is introduced to assist perovskite growth. Di‐tert‐butyl(methyl)phosphonium tetrafluoroborate is introduced into the precursor to form a low‐solubility complex with PbI2, which serve as seed to induce perovskite crystallization during solvent evaporation. The hetero‐SiC process is a proven effective way to manipulate the nucleation process and crystal growth, visualized by several in situ measurement tools.